2004
DOI: 10.1080/01674820400017905
|View full text |Cite
|
Sign up to set email alerts
|

Psychological group support attenuates distress of waiting in couples scheduled for assisted reproduction

Abstract: The aim of the study is to determine whether a cognitive-behavioral group treatment could lead to a decrease of psychological distress in couples waiting for assisted reproduction. Fifty consecutive couples included in the waiting list for IVF-ET or ICSI were randomly allocated either to receive Cognitive-Behavioral Treatment (CBT Group) or just waiting (Observation Group). The group is formed by 8-10 couples; 12 meetings are provided for a period of 4 months. Two psychometric test have been administered (Symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 22 publications
0
27
1
2
Order By: Relevance
“…However, a significant decrease in the use of escape/avoidance coping strategies was reported in the intervention group. On the contrary, in the studies conducted by Van Zyle et al and Tarabusi et al, no statistically significant differences were reported in terms of the escape from stressors or avoidance coping strategy (25,27). In the present study, the women used the escape/avoidance coping strategy less frequently due to participation in the counseling sessions, involvement in the treatment process and familiarity with the coping strategies.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…However, a significant decrease in the use of escape/avoidance coping strategies was reported in the intervention group. On the contrary, in the studies conducted by Van Zyle et al and Tarabusi et al, no statistically significant differences were reported in terms of the escape from stressors or avoidance coping strategy (25,27). In the present study, the women used the escape/avoidance coping strategy less frequently due to participation in the counseling sessions, involvement in the treatment process and familiarity with the coping strategies.…”
Section: Discussioncontrasting
confidence: 52%
“…Similarly, Karlsen et al and Tarabusi et al reported that the intervention and control groups had no differences in the planning and active coping subscales (26,27). However, Fife et al reported a significant increase in the use of active coping in the intervention group.…”
Section: Discussionmentioning
confidence: 91%
“…A variety of psychosocial interventions, such as cognitive behavioural therapy [9][10][11], mind body intervention [12][13][14], counselling [15][16][17][18] and positive reappraisal coping therapy [19,20], have been adopted to improve the mental health, pregnancy rates and marital function of couples who undergo IVF treatment. However, in a review of the literature, the effects of relevant interventions tested in randomized controlled trial studies could not be confirmed due to methodological or practical issues [21].…”
Section: Introductionmentioning
confidence: 99%
“…Although Bringhenti et al [29] and Lovely et al [30] found no association between stress and infertility, many studies have shown that women undergo more stress during in-vitro fertilization procedures than men, whose self-esteem is higher owing to less psycho-cognitive damage [17,[24][25][26][27][28]. Moreover, some studies have reported that stress could decrease through psycho-cognitive and behavioral-cognitive treatment, especially during in-vitro fertilization cycles [31][32][33][34]. It seems that the findings of the present study are in agreement with prior research, but they do not confirm the results of the studies by Bringhenti et al [29] or Lovely et al [30].…”
Section: Discussionmentioning
confidence: 98%